SHM_3271258_3D Vendel Fragment: Helmet Crest Decorative Detail - Bonnevier, Helena; Lernestål, Erik; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a fragment of decorative detail from a helmet crest from the Vendel period. Excavated from Vendel Boat Grave XI/Boat Grave 11 in Vendel, Uppsala, it is currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collections platform

https://dyncoll.ht.lu.se/artifact_view.php?item=981

Link to Sök I Samlingarna

https://samlingar.shm.se/object/9db73ba5-0e86-4e76-b992-14eff58936d2
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Photogrammetry; 3D Model; Museum Object; Dynamic Collections; Vendel; Vendel Period; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi